Medição do perfil de velocidade por técnica ultrassônica utilizando o método da autocorrelação estendida e equipamento para ensaios não destrutivos - Ofuchi, César Yutaka (2016)
Interest in knowing the instantaneous velocity profile in fluid dynamics has grown in recent years as new flow visualization techniques are improving. In this context, the ultrasonic Doppler velocity profiler (UVP) has desirable characteristics, as it is non-invasive, works with opaque liquids, and it is portable and easy to install if compared with other velocity profiler methods. In this work, the use of nondestructive ultrasonic devices in the UVP field is investigated. NDT systems are widely available and have lower cost if compared to traditional ultrasonic velocity profiler systems. The use of an extended autocorrelation method (EAM) for ultrasonic velocity estimation beyond Nyquist limit are also evaluated. The Nyquist limit causes a restriction on the maximum measurable velocity of the traditional autocorrelation method (ACM), present in most of ultrasonic velocity profiler systems. EAM combines the ACM technique with cross-correlation method (CCM) which is a well-established velocity estimator that does not suffer with Nyquist limit. However, the technique has a high computational cost that limits real time applications. EAM has the advantage of measure velocities beyond the Nyquist limit but with a lower computational cost than CCM. To evaluate the NDT device and the velocity estimation techniques ACM, CCM and EAM, a data acquisition system and a signal-processing unit based on LabView language were developed. The velocity profile of a rotating cylinder was used to validate all measurements. The techniques ACM, CCM and EAM successfully measured velocities within Nyquist limit with less than 2% deviation, validating the NDT system. EAM also measured velocities beyond Nyquist limit with a computational performance 9 times faster than CCM. The ultrasonic technique was also applied to measure the velocity profile of a multiphase flow in a pipeline, which are of great interest in oil and gas industry. Tests within a multiphase flow composed by different combinations of oil/sand/nylon-particles and gas were conducted in a vertical rig. A high-speed camera was used to validate the measurements. First the ultrasonic velocity profile measured was validated in a liquid-solid flow by using a Coriolis flowmeter as a reference. Next, superficial liquid and gas velocity were controlled to obtain different flow patterns such as bubbly flow and slug flow. The technique measured the bubbles velocity, the mixture velocity and the liquid film velocity depending on the flow pattern. Finally, the ultrasonic NDT system was successfully applied to investigate two different fluid engineering problems.